2019
DOI: 10.1186/s12987-019-0127-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extradural constriction on CSF flow in rat spinal cord

Abstract: BackgroundFluid homeostasis in the central nervous system (CNS) is essential for normal neurological function. Cerebrospinal fluid (CSF) in the subarachnoid space and interstitial fluid circulation in the CNS parenchyma clears metabolites and neurotransmitters and removes pathogens and excess proteins. A thorough understanding of the normal physiology is required in order to understand CNS fluid disorders, including post-traumatic syringomyelia. The aim of this project was to compare fluid transport, using qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…CSF flow obstruction in the spinal subarachnoid space has been suggested to increase pressure and thus force fluid into the cord [9][10][11]. Indeed, in a recent rodent study, a spinal subarachnoid space obstruction increased CSF tracer penetration in spinal cord tissue [12]. This finding aligns with the observation that most post-traumatic syrinxes are associated with narrowing or obstruction of the spinal subarachnoid space [2].…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…CSF flow obstruction in the spinal subarachnoid space has been suggested to increase pressure and thus force fluid into the cord [9][10][11]. Indeed, in a recent rodent study, a spinal subarachnoid space obstruction increased CSF tracer penetration in spinal cord tissue [12]. This finding aligns with the observation that most post-traumatic syrinxes are associated with narrowing or obstruction of the spinal subarachnoid space [2].…”
Section: Introductionsupporting
confidence: 61%
“…2). Enlarged perivascular spaces are hypothesized to occur from perturbations to subarachnoid CSF flow, and may increase the fluid load of the cord [12]. Indeed, enlarged perivascular spaces have been observed in syringomyelia in human [43], and in animal models [16,20].…”
Section: Discussionmentioning
confidence: 99%
“…These diseases all lead to changes in the fluid dynamics of CSF in the subarachnoid space, thus favoring the flow of CSF from the subarachnoid space into the central canal [ 29 , 30 ]. Some studies have confirmed that CSF passes through the spinal cord to communicate between the subarachnoid space and central canal [ 13 , 26 , 31 33 ]. In our model, CSF flow was blocked due to extradural compression.…”
Section: Discussionmentioning
confidence: 99%
“…We still do not understand why only some nerve roots in some of the animals were observed. Although it has been described that experimental SSAS obstruction may result in disruption of cervical lymphatic drainage at spinal nerve root sheaths, 25 we found no relationship between the observability of roots and experimental groups. We speculate that variables such as anatomical variants of the nerve root sheath, 24,26 variations in breathing conditions, 27 and differences in intrathecal pressure could be involved in the selectivity of neuroimaging nerve root enhancement.…”
Section: Discussionmentioning
confidence: 98%